Penerapan Metode Pembelajaran Resitasi dalam Pembelajaran Matematika Dasar - Ismatullah, Kholida (Jurnal Pendidikan Informatika (EDUMATIC), 2017)
The purpose of this study is to describe: (1) Application of recitation methods on learning mathematics; (2) Positive impact of using recitation method on learning mathematics; (3) The disadvantages of recitation methods in mathematics learning. This research uses qualitative approach of descriptive type. Research location at Hamzanwadi University. The study was conducted in October until November 2017. Population in this research is student of study program of Informatics, while the sample is student of study program of Informatics which amounted to 39 people. The techniques of data collection used are observation, interview and document analysis. The results of this study show that: (1) The application of recitation method in mathematics learning starts from the phase of assignment, assignment and accountability of tasks that have been made; (2) Positive impact of recitation method on learning mathematics among others: improving student creativity, fostering student responsibilities, improving students' mathematical communication skills, and providing new experiences to students; (3) The disadvantages of recitation methods in learning mathematics include: the lack of student participation, the difficulty of controlling and supervising the tasks undertaken by students, different levels of student intelligence, and the limited carrying capacity or available facilities.